Antimicrobial resistance in Indian isolates of non typhoidal Salmonella of livestock, poultry and environmental origin from 1990 to 2017. (January 2022) - Inbaraj, Sophia; Agrawal, Ravi Kant; Thomas, Prasad; Mohan, Chandra; Agarwal R.K, S.; Verma, Med Ram; Chaudhuri, Pallab
Abstract: A retrospective antimicrobial resistance study of nontyphoidal Salmonella enterica isolates from India during 1990–2017 was conducted to study the microbial susceptibility to antibiotics. A total of 271 Salmonella enterica isolates from poultry (n = 146), farm animals (n = 55) and environmental sources (n = 70) were tested for susceptibility using 15 antimicrobial drugs. The drug classes include aminoglycosides, phenicols, cephalosporins, penicillins, carbapenems, fluoroquinolones, and sulphonamide-trimethoprim. Study revealed that overall, 133 (49.08%) of 271 isolates were resistant to ≥ 1 antimicrobial drugs and 81 (29.89%) out of 271 isolates were multidrug resistant (resistance to ≥ 3 drugs). Majority (68.96%) of Typhimurium serovars (n = 87) were susceptible to all antibiotics tested, whereas only 5% Kentucky serovars (n = 40) were pan susceptible. All the drugs revealed decreasing trend of susceptibility from 1990 towards 2017 except cephalosporins and carbapenems. Statistical analysis of association between time period and antimicrobial resistance revealed a significance of < 0.05. Molecular detection of genetic determinants associated with antimicrobial resistance revealed the presence of genes like class I integrons, sul1, sul2, catIII, cmlA, dfrA, bla TEM, bla AmpC in the resistant isolates. Furthermore, plasmid mediated quinolone resistant determinants like qnrD and qnrS were also reported in the current study. Highlights: Antimicrobial resistance studies in Indian isolates of non typhoidal Salmonella were done. Study revealed that 30% isolates were multidrug resistant. Resistance to fluloquinolones like ciprofloxacin and levofloxacin emerged after 2010. A rare plasmid mediated resistant determinant, namely, qnrD was reported in poultry isolates.